2015
DOI: 10.1111/sms.12389
|View full text |Cite
|
Sign up to set email alerts
|

Sprint mechanics in world‐class athletes: a new insight into the limits of human locomotion

Abstract: The objective of this study was to characterize the mechanics of maximal running sprint acceleration in high-level athletes. Four elite (100-m best time 9.95-10.29 s) and five sub-elite (10.40-10.60 s) sprinters performed seven sprints in overground conditions. A single virtual 40-m sprint was reconstructed and kinetics parameters were calculated for each step using a force platform system and video analyses. Anteroposterior force (FY), power (PY), and the ratio of the horizontal force component to the resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
473
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(518 citation statements)
references
References 37 publications
39
473
6
Order By: Relevance
“…Many studies have examined the mechanics of linear sprinting, with the majority focusing on spatiotemporal variables. The fastest runners maximize their acceleration and maximum sprinting velocities by applying greater mass-specific ground forces, [1][2][3] but research literature has so far provided limited information regarding how sprinting athletes should optimize their movements. Due to technology limitations, experimental kinematic studies have typically focused on the measurement area either around the start, [4][5][6] the acceleration phase [7][8][9][10] or during the maximal velocity phase, [11][12][13] typically assessing 1-3 steps.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the mechanics of linear sprinting, with the majority focusing on spatiotemporal variables. The fastest runners maximize their acceleration and maximum sprinting velocities by applying greater mass-specific ground forces, [1][2][3] but research literature has so far provided limited information regarding how sprinting athletes should optimize their movements. Due to technology limitations, experimental kinematic studies have typically focused on the measurement area either around the start, [4][5][6] the acceleration phase [7][8][9][10] or during the maximal velocity phase, [11][12][13] typically assessing 1-3 steps.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the assumption that maximal speed phase included 20 strides, they concluded that 0.06-0.08 s could be taken off a sprinter's time [5]. Rabita et al [6] focused their investigation on the biomechanics involved in the sprint acceleration phase. Nine sprinters (ages 23.9 + 3.5 years) ranging in expertise, completed several short sprints (10 m, 15 m, 20 m, 30 m and 40 m) using force plates (piezoelectric sensor 1.2 × 0.6 m) to obtain the GRFs.…”
Section: Introductionmentioning
confidence: 99%
“…Within sprinting research IMUs have been determined to be both accurate and reliable to determine the stance duration [8]. A single lower back mounted IMU was validated against retro-reflective motion capture (Vicon, Yarnton, Oxford, UK) and shown to reliably find angular displacement and velocity during sprinting [6]. Further to this, Philpott et al [2] used block mounted force plates and Vicon for sprinting starts finding the timing accurate to 0.025 ± 0.024 s, a number which may have been reduced if a higher sampling frequency (50 Hz) was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, sprinters are required to produce high amounts of explosive power (i.e. P M ) during push-off phase on the staring block (Harland & Steele, 1997;Rabita et al, 2015), as well as the ability to produce relatively higher force at high velocity movements (i.e. V 0 ) that prevent premature force decline over the acceleration phase and maintain relatively higher force production at maximal speed .…”
Section: Force-velocity Profiles Of Elite Athletes | P R Bozic and Bmentioning
confidence: 99%